Efficacy of micro-encapsulated of local isolate B. thuringiensis as bio-insectiside for control of myiasis caused by Chrysomya bezziana larvae - Muharsini S; Wardhana AH (Indonesian Center for Animal Research and Development (ICARD), 2014)
B. thuringiensis produces toxic crystal proteine (-endotoksin) which is specific for insect target, but non-toxic to human or non-target organism. Local isolate of B. thuringiensis have been collected from Kediri Regency where endemic area of myiasis. The aim of this study was to formulate the micro-encapsulated of B. thuringiensis using Freund Incomplete Adjuvant (FIA) for protecting crystal in the field and enviromentally friendly. The formulae was then tested in vitro and in vivo. The result of in vitro trial towards seven local isolates of B. thuringiensis showed a decreased in the toxicity of those several isolates. In vivo trial of nine thin tail sheep using chosen isolat of 45.5A and 47.3A, resulted is no significant different for treatment sheep compared to control sheep (P > 0.05). It is concluded that micro-encapsulation method need to be developed according to the way of living the C. bezziana larvae in animal tissues. Key Words: Chrysomya bezziana, Bacillus thuringiensis, Freund Incomplete Adjuvant, Micro-encapsulated